The Paget's disease of bone risk gene PML is a negative regulator of osteoclast differentiation and bone resorption - Sachin Wani; Anna Daroszewska; Donald M. Salter; Rob J. van 't Hof; Stuart H. Ralston; Omar M. E. Albagha (The Company of Biologists, 2022)
Paget's disease of bone (PDB) is characterized by focal increases in bone remodelling. Genome-wide association studies identified a susceptibility locus for PDB tagged by rs5742915, which is located within the PML gene. Here, we have assessed the candidacy of PML as the predisposing gene for PDB at this locus. We found that the PDB-risk allele of rs5742915 was associated with lower PML expression and that PML expression in blood cells from individuals with PDB was lower than in controls. The differentiation, survival and resorptive activity of osteoclasts prepared from Pml−/− mice was increased compared with wild type. Furthermore, the inhibitory effect of IFN-γ on osteoclast formation from Pml−/− was significantly blunted compared with wild type. Bone nodule formation was also increased in osteoblasts from Pml−/− mice when compared with wild type. Although microCT analysis of trabecular bone showed no differences between Pml−/− mice and wild type, bone histomorphometry showed that Pml−/− mice had high bone turnover with increased indices of bone resorption and increased mineral apposition rate. These data indicate that reduced expression of PML predisposes an individual to PDB and identify PML as a novel regulator of bone metabolism. This article has an associated First Person interview with the first author of the paper.